4D‐CT for Localization of Nonlocalizing Parathyroid Adenomas in Primary Hyperparathyroidism. (2nd September 2014) - Hobbs, Bradley A.; Fitzgerald, Ryan; Bodenner, Donald L.; Stack, Brendan C.
Abstract : Objectives: (1) Present the application of 4‐dimensional (4D) computed tomography (CT) in preoperative localization of parathyroid adenomas that do not localize with technetium‐99 (Tc‐99) single‐photon emission computed tomography (SPECT)/CT or ultrasound. (2) Present indications for 4D‐CT use. (3) Understand radiologic dosimetry issues of 4D‐CT. Methods: A retrospective review of over 15 consecutive patients at an academic medical center with primary hyperparathyroidism who underwent preoperative 4D‐CT after nonlocalizing preoperative ultrasound and Tc‐99 SPECT‐CT scans between November 2013 and June 2014. This was a mixture of patients presenting for their first operations and others requiring revision surgery. Intraoperative radioguided parathyroidectomy results, excised gland weight, patient demographics, and parathyroid hormone levels were recorded. Sensitivity, specificity, and positive and negative predictive values of 4D‐CT for preoperative adenoma localization were calculated. Results: 4D‐CT resulted in successful localization and biochemical cure in all primary or revision cases in which it was utilized. Radiation doses from 4D‐CT will be presented and compared to radiologic dosimetry from SPECT‐CT. Conclusions: 4D‐CT offers a sensitive and specific modality for preoperative parathyroid adenoma localization which is useful in cases where ultrasound and SPECT‐CT sestamibi are nonlocalizing.